Particle Image Velocimetry Analysis On Simple Soil-Structured Interaction - Lau, See Hung (Universiti Malaysia Sarawak (UNIMAS), 2010)
Particle Image Velocimetry (PIV) has been widely used in fluids analysis. Studies have been carried out to adapt the image processing method into physical characteristics of soil displacement in geotechnical engineering. This study focused on the applications of PIV into measuring and observing the profile for soil displacement under various loadings and shapes of the foundation. An experimental set-up for the study was modeled and designed accordingly with the aids from previous studies and PLAXIS software. The validation and experimental test set-up were then used to carry out the study on camera calibration as well as on simple soil-structure interaction. In MatPIV analysis, cross-correlation method is applied to detect the difference of pixels in a window for the soil particles in an image. The validation and experimental test setup were used to study on the validity of the measurements as well as to attain the mode and magnitude of soil displacement and strain analysis in a simple soil-structure interaction study. A total of 70 displacement data were studied in the validation test. It showed that an accuracy of 98.8% could be measured using the MatPIV analysis when compared to the measured displacement using the LVDT. The validation test justifies the suitability of adapting MatPIV into soil displacement measurement with high accuracy.